Urethral dilatation: Is there any benefit over cystoscopy and distension? A randomized trial in women with overactive bladder symptoms. Issue 3 (1st May 2013) - Basu, Maya; Khullar, Vik; Duckett, Jonathan
Abstract Aim To evaluate the effect of urethral dilatation (UD) on urgency symptoms in women with overactive bladder (OAB) and voiding dysfunction. Methods Women with OAB symptoms and a maximum flow rate of less than 15 ml/sec on a volume voided of 200 ml were eligible for entry to the trial. Fifty women with OAB symptoms and a maximum flow rate of less than 15 ml/sec on a volume voided of over 200 ml were randomized to undergo UD plus cystoscopy or cystoscopy alone. All subjects underwent filling and voiding cystometry pre‐operatively and at 6 weeks' post‐operatively. Subjective outcomes were assessed using the Urgency Perception Scale (UPS) and King's Health Questionnaire at baseline, 6 weeks and 6 months. The primary outcome measure was cure of urgency, defined using the UPS. Results Urgency was cured in 10/22 (45%) patients in the UD group and 5/28 (18%) in the non‐UD group at 6 weeks (Odds ratio 3.8, 95% confidence interval 1.1–13.8, P = 0.03). Cystometric flow data were available for all patients pre‐ and post‐UD. UD was associated with a significant increase in the flow rate centile from 1.66 to 8.54 (P = 0.01). At 6 months there was no benefit from UD with 4/22 in the UD group cured of urgency and 4/28 in the non‐UD group cured (Odds ratio 1.3, 95% confidence interval 0.3–6.1, P = 0.50). Conclusion UD confers a significant short‐term benefit in cure of urgency over cystoscopy alone, but there is no significant benefit in symptom relief in the long term. Neurourol. Urodynam. 33:283–288, 2014. © 2013 Wiley Periodicals, Inc.